Intelligent adjustable baby diaper
By using composite hydrotonic nonwoven materials, composite plant essence fibers and highly absorbent resin fibers in baby diapers, the problem of existing baby diapers neglecting the environment and skin health is solved, and the dryness and breathability are achieved. Sex and comfort and reduce the risk of diaper rash.
Patent Information
- Application Number
- CN202411334705.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-31
AI Technical Summary
Existing baby diapers ignore the impact on the environment and monitoring of infant skin health during long-term use. The slow absorption of cotton fibers may lead to urine respiration, increase the risk of diaper rashes, and poor elasticity of viscose fibers affects wear comfort.
Using intelligent adjustment baby diapers, including the surface layer consists of composite hydrotonic nonwoven material and release layer consists of composite plant essence fiber material, the guide layer contains PVA fiber and PNIPAM, and the absorbent core is composed of highly absorbent resin and wood pulp fiber. The back layer is a breathable microporous membrane, which enhances the performance of the material through ultrasonic bonding and antibacterial finishing.
It improves dryness and breathability, reduces back seepage, prevents diaper rash, provides a more comfortable wearing experience, uses bio-based materials to reduce environmental impact, and has intelligent adjustment function to adapt to different conditions.
Smart Images

Figure CN119214868A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of baby diapers, in particular to intelligently adjustable baby diapers. Background Art
[0002] Baby diapers are generally composed of an outer layer / bottom film, an absorption layer, a guide layer, a surface layer, an elastic waist and leg leak-proof edges. The absorbent core is the main part of the diaper, which is used to absorb and store liquid. It is generally composed of a mixture of super absorbent resin (SAP) and wood pulp fibers. Super absorbent resin can absorb and lock a large amount of liquid, while wood pulp fibers help the liquid to spread quickly. Some products may use a composite core design, that is, the entire core is made of SAP. There are also full cores that combine fluff pulp and SAP to achieve better absorption effects.
[0003] The current baby diapers on the market, including pants-type diapers, focus more on the absorption speed and absorption capacity of the absorption core and the overall wearing comfort of the diapers, but often ignore the impact of long-term use on the environment and the monitoring of baby skin health; the surface layer of the diaper is in direct contact with the baby's skin, generally made of cotton fiber or viscose fiber. Cotton fiber has natural, soft, skin-friendly properties, is friendly to baby's skin, and has good breathability. However, the water absorption speed of cotton fiber is relatively slow, which may cause urine to stay on the surface for a long time, increasing the possibility of back-seepage, thereby affecting the baby's comfort and skin health. In addition, cotton fiber is easy to become a breeding ground for bacteria in a humid environment, especially when the baby's excrement contains bacteria, which increases the risk of diaper rash. Viscose fiber has strong hygroscopicity and can quickly absorb liquid, but viscose fiber has general elasticity, that is, poor softness, and may not be able to adapt well to the baby's various activities, causing discomfort or leakage, affecting the fit and comfort of wearing;
[0004] Therefore, it is an urgent need to develop a baby diaper that prevents baby skin from getting wet and is comfortable. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an intelligent adjustable baby diaper.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The intelligent adjustable baby diaper comprises a diaper body, wherein the diaper body comprises, from inside to outside:
[0008] Surface layer: including a contact layer and a release layer. The contact layer is in direct contact with the baby's skin and is responsible for cleaning and absorption. The release layer is located under the contact layer and contains skin care ingredients. The contact layer and the release layer are fixed by ultrasonic bonding.
[0009] Diversion layer: absorbs the liquid in the surface layer and diffuses it downward, including absorption fibers, diversion fibers and regulating fibers;
[0010] Absorbent core: absorbs and locks urine, made of a composite of highly absorbent resin and wood pulp fiber;
[0011] Back layer: It is composed of a breathable microporous membrane and a bottom layer.
[0012] As a preferred technical solution of the present invention, the contact layer includes:
[0013] The upper layer is composed of a composite spunlace nonwoven material, which is composed of cotton fiber, polylactic acid fiber and cellulose nanofiber material. The total weight of the upper layer is 100%, and the cotton fiber, polylactic acid fiber and cellulose nanofiber account for 40-60%, 30-50% and 5-10% respectively.
[0014] Lower layer: composed of viscose spunlace nonwoven material made of viscose fibers.
[0015] As a preferred technical solution of the present invention, the release layer is made of composite plant essence fiber material;
[0016] The composite plant essence fiber material comprises aloe fiber, jojoba oil essence fiber and shea butter essence fiber. Taking the total weight of the composite plant essence fiber material as 100%, the proportions of aloe fiber, jojoba oil essence fiber and shea butter essence fiber are 40-50%, 20-30% and 20-30% respectively.
[0017] The composite plant essence fiber material is subjected to antibacterial finishing.
[0018] As a preferred technical solution of the present invention, the preparation steps of the composite spunlace nonwoven material are as follows:
[0019] A1: Wash and dry the polylactic acid fiber for pretreatment, and loosen, remove impurities and comb the cotton fiber for pretreatment;
[0020] A2: adding the pretreated polylactic acid fiber and cotton fiber into a mixer according to a certain proportion and mixing them. The mixer speed is 40-80 r / min, the mixing time is 5-10 min, and the relative humidity is controlled at 30-60% to obtain a mixture 1;
[0021] A3: Keeping the mixture 1 in a mixing state in the mixer, adding cellulose nanofiber powder to the mixture 1, and continuing to mix for 5-10 minutes to obtain a mixture 2;
[0022] A4: Use a carding machine to card the mixture into a fiber web, and lay the carded fiber web on a conveyor belt to obtain an upper fiber web layer;
[0023] A5: Use a hydroentanglement reinforcement machine to reinforce the upper fiber mesh layer, the water flow pressure is 50-200 bar, and the water flow impact time in each area is 5-30 seconds to obtain product 1;
[0024] A6: Use a point-shaped thermal bonding machine to perform local thermal bonding on product 1, the thermal bonding temperature is 150-180°C, and the time for each bonding point is 10-60ms to obtain product 2;
[0025] A7: Dry, cut and slit the second product to finally obtain a composite spunlace nonwoven material.
[0026] As a preferred technical solution of the present invention, the preparation steps of the viscose spunlace nonwoven material are as follows:
[0027] B1: opening, combing and laying the viscose fibers to obtain a lower fiber web layer;
[0028] B2: The lower fiber web layer is pre-treated by spray wetting, and then reinforced by a hydroentanglement reinforcement machine, with a water flow pressure of 50-200 bar and a water flow impact time of 5-30 seconds in each area, to obtain an initial lower layer;
[0029] B3: The initial lower layer is subjected to vacuum water absorption and hot air drying treatment at a drying temperature of 80-120° C., and finally cut and slit to obtain a viscose spunlace nonwoven material.
[0030] As a preferred technical solution of the present invention, the steps of preparing the contact layer are as follows:
[0031] C1: 40-60g / m 2 The viscose spunlace nonwoven material is laid flat, and the composite spunlace nonwoven material is superimposed on the surface of the viscose spunlace nonwoven material to obtain a superimposed layer;
[0032] C2: Use a bonding machine to bond the four sides of the stacked layer, and use a laser etching machine to punch holes, with a mesh diameter of 2-4 mm and a mesh spacing of 0.3-0.8 mm, to finally obtain a contact layer.
[0033] As a preferred technical solution of the present invention, the antibacterial finishing steps of the composite plant essence fiber material are as follows:
[0034] D1: Add tea polyphenol solid powder into a container, add deionized water, stir and dissolve to prepare a tea polyphenol solution;
[0035] D2: Add nano zinc oxide powder and polyethyleneimine to the tea polyphenol solution and stir, and use an ultrasonic oscillator to stir for 3-10 minutes to obtain a mixed solution;
[0036] D3: Immerse the composite plant essence fiber material in the mixed solution for 8-12 hours, then take it out and dry it at a temperature of 50-70°C for 20-40 minutes.
[0037] As a preferred technical solution of the present invention, in the guide layer:
[0038] The absorbent fibers include cotton fibers and super absorbent resin fibers, which account for 50-60% and 40-50% respectively, based on the total weight of the absorbent fibers themselves being 100%;
[0039] The flow-guiding fibers include polyester fibers and polypropylene fibers, which account for 50-60% and 40-50% respectively, based on the total weight of the flow-guiding fibers themselves being 100%;
[0040] The regulating fiber is polyvinyl alcohol fiber and poly N-isopropyl acrylamide material, and the proportions are 60-70% and 30-40% respectively, based on the total weight of the regulating fiber itself being 100%;
[0041] Taking the total weight of the guide layer as 100%, the proportions of absorption fibers, guide fibers and regulating fibers are 35-45%, 35-45% and 10-20% respectively.
[0042] As a preferred technical solution of the present invention, the preparation steps of the guide layer are as follows:
[0043] E1: Pour the absorbent fiber and the diversion fiber into a container according to a proportion, and mix them using a mixer to obtain a mixed material;
[0044] E2: Spreading the mixed material into a mesh structure through an opener and a carding machine to obtain a mesh material;
[0045] E3: The mesh material is melted by heating and pressurizing, and a firm connection is formed after cooling to obtain a molding material 1;
[0046] E4: combing the adjusted fibers and performing heating and pressurizing treatment to obtain a second molding material;
[0047] E5: Lay the molding material 1 flat on the molding material 2, and bond the molding material 1 and the molding material 2 by a laminating machine to obtain an initial guide layer;
[0048] E6: Fix the initial guide layer on the workbench, use a laser punching machine to punch holes on its surface, and finally obtain the guide layer.
[0049] As a preferred technical solution of the present invention, the production process of the diaper body is as follows:
[0050] F1: Unwind the backing layer from the unwinder and lay it on the production line;
[0051] F2: Lay the absorbent core on the surface of the back layer and extrude it using a molding machine to form a molded composite body;
[0052] F3: Lay the guide layer flat on the surface of the composite body 1, and bond the guide layer and the composite body 1 by a laminating machine to obtain the composite body 2;
[0053] F4: Lay the surface layer flat on the surface of the second composite body, bond the surface layer and the second composite body together through a laminating machine, and cut and trim them to obtain a diaper main body.
[0054] The present invention has the following beneficial effects:
[0055] 1. Enhanced dryness: By using composite spunlace nonwoven materials as the contact layer, which contains cotton fibers, polylactic acid fibers and cellulose nanofibers, this combination can quickly conduct liquids, and the presence of cellulose nanofibers increases the porosity and optimizes the liquid conduction path. In addition, PVA fibers and PNIPAM are added to the guide layer. These materials can increase the water absorption speed and reduce the back seepage, making the overall product better than traditional diapers in terms of absorption performance;
[0056] 2. Improve skin health: The contact layer not only takes into account the rapid conduction of liquids, but also has a specially designed release layer, which contains aloe vera fiber, jojoba oil essence fiber and shea butter essence fiber. These are skin-friendly ingredients that help prevent diaper rash, reduce skin inflammation, and keep the skin moisturized and comfortable. The antibacterial finishing step uses tea polyphenols and zinc oxide to enhance the antibacterial properties of the material, help inhibit bacterial growth, and protect the baby from infection risks.
[0057] 3. Breathability and softness: The contact layer is made of fibers mixed in a specific ratio, which ensures good liquid transmission and good breathability. Experimental data show that the air permeability of samples 1 to 3 is higher than that of sample 6 made of viscose fiber only, indicating that it is more conducive to keeping the baby's skin dry and comfortable. The use of cellulose nanofibers and other natural fibers improves the overall softness of the material, providing a more comfortable wearing experience for babies.
[0058] 4. Environmentally friendly: Use bio-based materials such as polylactic acid fibers, which are usually biodegradable or derived from sustainable resources, reducing the impact on the environment and meeting the current consumer preference for environmentally friendly products;
[0059] 5. Intelligent adjustment function: PNIPAM in the guide layer is temperature-sensitive, which enables it to automatically adjust its water absorption capacity and water release behavior under different conditions, further enhancing the adaptability and functionality of the diaper. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 This is a schematic diagram of the structure of the intelligent adjustable baby diaper proposed by the present invention;
[0061] Figure 2 is a flow chart for the preparation of the contact layer;
[0062] Figure 3 The preparation flow chart of the guide layer. DETAILED DESCRIPTION
[0063] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0064] Reference Figure 1-3 , the intelligent adjustable baby diaper comprises a diaper body, and the diaper body is composed of the following from the inside out:
[0065] Surface layer: including contact layer and release layer. The contact layer is in direct contact with the baby's skin and is responsible for cleaning and absorption. The release layer is located under the contact layer and contains skin care ingredients. The contact layer and the release layer are fixed by ultrasonic bonding.
[0066] Diversion layer: absorbs the liquid in the surface layer and diffuses it downward, including absorption fiber, diversion fiber and regulation fiber;
[0067] Absorbent core: absorbs and locks urine, made of a composite of highly absorbent resin and cotton fiber;
[0068] Back layer: It is composed of a breathable microporous membrane and a bottom layer.
[0069] The contact layer includes an upper layer and a lower layer. The upper layer is composed of a composite spunlace nonwoven material, which is composed of cotton fiber, polylactic acid fiber and cellulose nanofiber material. The total weight of the upper layer is 100%, and the cotton fiber, polylactic acid fiber and cellulose nanofiber account for 40-60%, 30-50% and 5-10% respectively; the lower layer is composed of a viscose spunlace nonwoven material made of viscose fiber.
[0070] The preparation steps of the composite spunlace nonwoven material are as follows:
[0071] A1: Wash and dry the polylactic acid fiber for pretreatment, and loosen, remove impurities and comb the cotton fiber for pretreatment;
[0072] A2: adding the pretreated polylactic acid fiber and cotton fiber into a mixer according to a certain proportion and mixing them. The mixer speed is 40-80 r / min, the mixing time is 5-10 min, and the relative humidity is controlled at 30-60% to obtain a mixture 1;
[0073] A3: Keeping the mixture 1 in a mixing state in the mixer, adding cellulose nanofiber powder to the mixture 1, and continuing to mix for 5-10 minutes to obtain a mixture 2;
[0074] A4: Use a carding machine to comb the mixture into a fiber web. Specifically, feed the mixture into a carding machine evenly, open and comb the mixture, so that the fibers gradually tend to be single fibers and adhere to the surface of the doffer. Then, the fiber web is peeled off by a stripping mechanism and wound onto an output roller to form a fiber web. Repeat the carding twice to obtain a relatively flat and uniform fiber web. The carding curtain speed is 3-5m / min. The carded fiber web is laid on a conveyor belt to obtain an upper fiber web layer.
[0075] A5: The upper fiber web layer is reinforced by a hydroentanglement machine, the water flow pressure is 50-200 bar, and the water flow impact time in each area is 5-30 seconds. Specifically, two hydroentanglement processes are adopted, namely, hydroentanglement-winding-unwinding-hydroentanglement, so that both sides of the fiber web are hydroentangled to obtain product 1;
[0076] A6: Use a point-shaped thermal bonding machine to perform local thermal bonding on product 1, the thermal bonding temperature is 150-180°C, and the time for each bonding point is 10-60ms to obtain product 2;
[0077] A7: Dry, cut and slit the second product to finally obtain a composite spunlace nonwoven material.
[0078] The preparation steps of viscose spunlace nonwoven material are as follows:
[0079] B1: opening, combing and laying the viscose fibers to obtain a lower fiber web layer;
[0080] B2: The lower fiber web layer is pre-treated by spray wetting, and then reinforced by a hydroentanglement reinforcement machine, with a water flow pressure of 50-200 bar and a water flow impact time of 5-30 seconds in each area, to obtain an initial lower layer;
[0081] B3: The initial lower layer is subjected to vacuum water absorption and hot air drying treatment at a drying temperature of 80-120° C., and finally cut and slit to obtain a viscose spunlace nonwoven material.
[0082] The steps for preparing the contact layer are as follows:
[0083] C1: 40-60g / m 2The viscose spunlace nonwoven material is laid flat, and the composite spunlace nonwoven material is superimposed on the surface of the viscose spunlace nonwoven material to obtain a superimposed layer;
[0084] C2: Use an ultrasonic bonding machine to bond the four sides of the stacked layer, and use a laser etching machine to punch holes with a mesh diameter of 2-4 mm and a mesh spacing of 0.3-0.8 mm to finally obtain a contact layer.
[0085] Embodiment 1
[0086] The contact layer prepared in this embodiment according to the above-mentioned contact layer preparation steps is specifically prepared as follows:
[0087] S1: Preparation surface density is 50g / m 2 The composite spunlace nonwoven material, the size of the carding machine is set to 500×700mm 2 , the raw material weight of the composite spunlace nonwoven material is 17.5g, and the proportions of cotton fiber, polylactic acid fiber and cellulose nanofiber are 50%, 40% and 10% respectively. 8.75g cotton fiber, 7g polylactic acid fiber and 1.75g cellulose nanofiber are weighed, and the cotton fiber and polylactic acid fiber are added to the mixer and mixed. The mixer speed is 50r / min, the mixing time is 8min, and the relative humidity is controlled at 50%. Then 1.75g cellulose nanofiber powder is poured into it and continued to mix for 8min to obtain a mixture. Then the mixture is combed at a combing speed of 3m / min, and then spunlace reinforcement is performed. The water flow pressure is 100bar, and the water flow impact time of each area is 20s. The edge position is thermally bonded using a point-shaped thermal bonding machine to improve the firmness of the overall structure. The thermal bonding temperature is 150℃, and the time of each bonding point is 30ms. Finally, it is dried at a drying temperature of 100℃ to obtain a composite spunlace nonwoven material, which is recorded as material a1;
[0088] S2: Preparation surface density is 50g / m 2 For viscose spunlace nonwoven materials, the size of the carding machine is set to 500×700mm 2 , weigh 17.5g of viscose fiber, open, card and lay the viscose fiber, use a spunlace reinforcement machine to reinforce it, the water flow pressure is 100bar, the water flow impact time in each area is 10s, and finally dry it at a drying temperature of 100℃ and a drying time of 10min to obtain a viscose spunlace nonwoven material, which is recorded as material b2;
[0089] S3: Lay the viscose spunlace nonwoven material flat, and stack the composite spunlace nonwoven material on the surface of the viscose spunlace nonwoven material to obtain a stacking layer. Use a bonding machine to bond the four sides of the stacking layer, and use a laser etcher to punch holes with a mesh diameter of 3 mm and a mesh spacing of 0.5 mm. Finally, a contact layer is obtained, which is recorded as sample one.
[0090] Embodiment 2
[0091] The contact layer prepared in this embodiment according to the above-mentioned contact layer preparation steps is specifically prepared as follows:
[0092] S1: Preparation surface density is 50g / m 2 Composite spunlace nonwoven material, the size of the carding machine card net is 500×700mm 2 , the raw material weight of the composite spunlace nonwoven material is 17.5g, and the proportions of cotton fiber, polylactic acid fiber and cellulose nanofiber are 60%, 30% and 10% respectively. Then 10.5g cotton fiber, 5.25g polylactic acid fiber and 1.75g cellulose nanofiber are weighed, and the cotton fiber and polylactic acid fiber are added to the mixer and mixed. The mixer speed is 50r / min, the mixing time is 8min, and the relative humidity is controlled at 50%. Then 1.75g cellulose nanofiber powder is poured into it and continued to mix for 8min to obtain a mixture. Then the mixture is combed at a combing speed of 3m / min, and then spunlace reinforcement is performed. The water flow pressure is 100bar, and the water flow impact time of each area is 20s. The edge position is thermally bonded using a point-shaped thermal bonding machine to improve the firmness of the overall structure. The thermal bonding temperature is 150℃, and the time of each bonding point is 30ms. Finally, it is dried at a drying temperature of 100℃ to obtain a composite spunlace nonwoven material, which is recorded as material b1;
[0093] S2: Preparation surface density is 50g / m 2 For viscose spunlace nonwoven materials, the size of the carding machine is set to 500×700mm 2 , weigh 17.5g of viscose fiber, open, card and lay the viscose fiber, use a spunlace reinforcement machine to reinforce it, the water flow pressure is 100bar, the water flow impact time in each area is 10s, and finally dry it at a drying temperature of 100℃ and a drying time of 10min to obtain a viscose spunlace nonwoven material, which is recorded as material b2;
[0094] S3: Lay the viscose spunlace nonwoven material flat, and stack the composite spunlace nonwoven material on the surface of the viscose spunlace nonwoven material to obtain a stacking layer. Use a bonding machine to bond the four sides of the stacking layer, and use a laser etcher to punch holes with a mesh diameter of 3 mm and a mesh spacing of 0.5 mm. Finally, a contact layer is obtained, which is recorded as sample two.
[0095] Embodiment 3
[0096] The contact layer prepared in this embodiment according to the above-mentioned contact layer preparation steps is specifically prepared as follows:
[0097] S1: Preparation surface density is 50g / m 2 Composite spunlace nonwoven material, the size of the carding machine card net is 500×700mm 2 , the raw material weight of the composite spunlace nonwoven material is 17.5g, and the proportions of cotton fiber, polylactic acid fiber and cellulose nanofiber are 40%, 50% and 10% respectively, then 7g cotton fiber, 8.75g polylactic acid fiber and 1.75g cellulose nanofiber are weighed, and the cotton fiber and polylactic acid fiber are added to the mixer and mixed, the mixer speed is 50r / min, the mixing time is 8min, the relative humidity is controlled at 50%, and then 1.75g cellulose nanofiber powder is poured therein, and the mixing is continued for 8min to obtain a mixture, and then the mixture is combed, and the combing net curtain speed is 3m / min, and then the spunlace reinforcement is performed, the water flow pressure is 100bar, and the water flow impact time of each area is 20s. The edge position is thermally bonded using a point-shaped thermal bonding machine to improve the firmness of the overall structure, the thermal bonding temperature is 150℃, and the time of each bonding point is 30ms. Finally, it is dried at a drying temperature of 100℃ to obtain a composite spunlace nonwoven material, recorded as material c1;
[0098] S2: Preparation surface density is 50g / m 2 For viscose spunlace nonwoven materials, the size of the carding machine is set to 500×700mm 2 , weigh 17.5g of viscose fiber, open, card and lay the viscose fiber, use a spunlace reinforcement machine to reinforce it, the water flow pressure is 100bar, the water flow impact time in each area is 10s, and finally dry it at a drying temperature of 100℃ and a drying time of 10min to obtain a viscose spunlace nonwoven material, which is recorded as material c2;
[0099] S3: Lay the viscose spunlace nonwoven material flat, and stack the composite spunlace nonwoven material on the surface of the viscose spunlace nonwoven material to obtain a stacking layer. Use a bonding machine to bond the four sides of the stacking layer, and use a laser etcher to punch holes. The mesh diameter is 3 mm and the mesh spacing is 0.5 mm. Finally, a contact layer is obtained, which is recorded as sample three.
[0100] Comparative Example 1
[0101] The difference between the contact layer provided in this comparative example and that in Example 1 is that:
[0102] The composite spunlace nonwoven material includes cotton fiber and polylactic acid fiber, each accounting for 50%. The preparation method and process parameters thereof refer to Example 1, and the contact layer finally obtained is recorded as Sample 4.
[0103] Comparative Example 2
[0104] The difference between the contact layer provided in this comparative example and that in Example 1 is that:
[0105] The composite spunlace nonwoven material contains only cotton fibers. The production steps are: opening, combing, spunlace reinforcement, local thermal bonding and drying of the cotton fibers. The parameters in the process are the same as those in Example 1. The obtained composite spunlace nonwoven material is recorded as material e.
[0106] The material e was fixed to the viscose spunlace nonwoven material in the same manner as in Example 1, and the contact layer finally obtained was recorded as Sample 5.
[0107] Comparative Example 3
[0108] The difference between the contact layer provided in this comparative example and that in Example 1 is that:
[0109] The contact layer component of this comparative example only contains viscose fiber, which is similar to the contact layer component of common diapers on the market. The production process is the same as the preparation steps of the above-mentioned viscose spunlace nonwoven material. The contact layer finally obtained is recorded as sample six.
[0110] The performance analysis of the above samples was carried out:
[0111] Specifically, carefully remove the surface layer of diapers of the same brand, model, and size, and cut off the elastic band and three-dimensional edge protection, leaving the absorbent core and the back layer. During the test, the contact layer materials of the diapers in Examples 1-3 and Comparative Examples 1-3 were laid on the same diapers with the surface layer removed;
[0112] Among them, the dryness test refers to the relevant standards of absorption speed and re-infiltration in GB / T28004.1-2011 "Diapers (sheets, pads)", using 0.9% sodium chloride solution as the test liquid, using a measuring cylinder to measure 80ml of the test solution, and starting the timing while pouring the liquid, recording the time when the test liquid is completely absorbed as the first infiltration time. After 5 minutes, repeat the operation, pour 80ml of the test solution again, and record the second infiltration time. After 10 minutes, quickly put a 20g round filter paper of appropriate size on the surface of the sample, and at the same time press a standard pressing block weighing 1.2kg onto the filter paper, restart the timing, remove the standard pressing block after 1 minute, and accurately weigh the mass of the filter paper with a balance, then the re-infiltration amount is the weight after the filter paper absorbs minus the weight before the filter paper absorbs;
[0113] The stiffness test was conducted using a YLL-201 electronic stiffness tester in accordance with GBT18318.1-2009 "Determination of flexural properties of textiles - Part 1: Inclined plane method". Six samples were randomly taken in the longitudinal and transverse directions of the material according to the sampling regulations. The sample size was 25×250mm. 2 , the smaller the bending length, the better the softness of the sample;
[0114] The air permeability test was conducted using a YG461 air permeability tester in accordance with the national standard GB / T5453-1997: Determination of air permeability of textiles. The test area was 20 cm 2 , the pressure is 100Pa, each sample is tested 10 times at different positions and the average value is taken;
[0115] The measurement results are shown in the following table:
[0116]
[0117] It can be seen from the above table that for the same amount of liquid, the absorption time and re-seepage amount of samples one, two, three, and four are less than those of samples five and six. Sample five has the highest air permeability and the best softness, while sample six has the lowest air permeability and the lowest softness. The air permeability and softness of samples one, two, three, and four are not much different from those of sample five, and are all greater than sample six. This is because polylactic acid fiber has good liquid conductivity and can quickly guide liquid to the absorbent core, thereby reducing the possibility of re-seepage. Taking all factors into consideration, adding polylactic acid fiber to the surface layer of diapers can improve the dryness of diapers and reduce the possibility of baby skin rashes.
[0118] Furthermore, the two absorption times and re-permeation amounts of samples 1, 2, and 3 are all less than those of sample 4, and the air permeability is better than that of sample 4. This is because cellulose nanofibers can increase the porosity of the material, optimize the liquid conduction path, and make the liquid penetrate from the surface faster. The microporous structure formed by the cellulose nanofibers can improve the air permeability of the material, thereby further improving the dryness of the diaper.
[0119] Furthermore, in terms of the two absorption times and the amount of rewet, sample three is less than sample one, and sample one is less than sample two. In terms of air permeability and softness, sample three is slightly worse than sample one, and sample one is slightly worse than sample two. This is because sample three has the highest content of polylactic acid fiber, which will help to quickly drain the liquid, and the presence of cellulose nanofibers can further optimize the structure and reduce rewet. Taking all factors into consideration, the dryness of the diaper can be optimized by adjusting the proportion of cotton fiber, polylactic acid fiber and cellulose nanofiber.
[0120] The release layer is made of composite plant essence fiber material;
[0121] The composite plant essence fiber material includes aloe fiber, jojoba oil essence fiber, and shea butter essence fiber. Taking the total weight of the composite plant essence fiber material as 100%, the proportions of aloe fiber, jojoba oil essence fiber, and shea butter essence fiber are 40-50%, 20-30%, and 20-30%, respectively, and the composite plant essence fiber material is antibacterial. Among them, aloe fiber contains a variety of active ingredients, such as polysaccharides, which help to reduce skin inflammation and prevent diaper rash. Among them, jojoba oil essence fiber contains antioxidants such as vitamin E, which helps to resist free radical damage and maintain skin health. Shea butter is rich in fatty acids and improves resistance to external stimuli such as moisture.
[0122] The antibacterial finishing steps of composite plant essence fiber material are as follows:
[0123] D1: Add tea polyphenol solid powder into a container, add deionized water, stir and dissolve to prepare a tea polyphenol solution;
[0124] D2: Add nano zinc oxide powder and polyethyleneimine to the tea polyphenol solution and stir, and use an ultrasonic oscillator to stir for 3-10 minutes to obtain a mixed solution;
[0125] D3: Immerse the composite plant essence fiber material in the mixed solution for 8-12 hours, then take it out and dry it at a temperature of 50-70°C for 20-40 minutes.
[0126] Tea polyphenols are a powerful natural antioxidant that can help resist free radical damage to skin cells and protect the skin from damage caused by environmental factors. Secondly, it has good anti-inflammatory properties, which can help reduce skin inflammation, reduce redness and discomfort, and is particularly helpful for preventing and relieving diaper rash. It can also help inhibit bacterial growth, keep the skin clean and hygienic, and reduce the risk of infection. Zinc oxide has a good soothing effect and can help relieve skin irritation, itching and burning sensations, while providing barrier protection for damaged skin. It also helps accelerate the wound healing process and has a certain therapeutic effect on minor skin damage or eczema. The release layer after the above-mentioned antibacterial finishing can regulate and protect the baby's skin.
[0127] In the diversion layer:
[0128] The absorbent fibers include cotton fibers and super absorbent resin fibers, which account for 50-60% and 40-50% respectively, based on the total weight of the absorbent fibers themselves being 100%;
[0129] The flow-guiding fibers include polyester fibers and polypropylene fibers, which account for 50-60% and 40-50% respectively, based on the total weight of the flow-guiding fibers themselves being 100%;
[0130] The regulating fibers are polyvinyl alcohol (PVA) fibers and poly N-isopropylacrylamide (PNIPAM) materials, and the proportions are 60-70% and 30-40% respectively, based on the total weight of the regulating fibers themselves being 100%.
[0131] Taking the total weight of the guide layer as 100%, the proportions of absorption fibers, guide fibers and regulating fibers are 35-45%, 35-45% and 10-20% respectively.
[0132] The preparation steps of the guide layer are as follows:
[0133] E1: Pour the absorbent fiber material and the diversion fiber material into a container according to a proportion, and mix them using a mixer to obtain a mixed material;
[0134] E2: Spreading the mixed material into a mesh structure through an opener and a carding machine to obtain a mesh material;
[0135] E3: The mesh material is melted by heating and pressurizing, and a firm connection is formed after cooling to obtain a molding material 1;
[0136] E4: Mixing, combing, heating and pressurizing the adjusted fiber materials according to proportions to obtain molding material 2;
[0137] E5: Lay the molding material 1 flat on the molding material 2, and bond the molding material 1 and the molding material 2 by a laminating machine to obtain an initial guide layer;
[0138] E6: Fix the initial guide layer on the workbench, use a laser punching machine to punch holes on its surface, and finally obtain the guide layer.
[0139] The production process of the diaper body is as follows:
[0140] F1: Unwind the backing layer from the unwinder and lay it on the production line;
[0141] F2: Lay the absorbent core on the surface of the back layer and extrude it using a molding machine to form a molded composite body;
[0142] F3: Lay the guide layer flat on the surface of the composite body 1, and bond the guide layer and the composite body 1 by a laminating machine to obtain the composite body 2;
[0143] F4: Lay the surface layer flat on the surface of the second composite body, bond the surface layer and the second composite body together through a laminating machine, and cut and trim them to obtain a diaper main body.
[0144] Embodiment 4
[0145] The surface density is 50g / m 2The guide layer of the carding machine is set to a size of 100×200mm. 2 The weight of the raw material for preparing the guide layer is 10g, and the proportions of absorbent fiber, guide fiber and regulating fiber are 40%, 40% and 20% respectively. Among the absorbent fibers, cotton fiber and super absorbent resin fiber each account for 50%, and among the guide fibers, polyester fiber and polypropylene fiber each account for 50%. Among the regulating fibers, polyvinyl alcohol fiber and poly (N-isopropylacrylamide) material account for 70% and 30% respectively. The weights of cotton fiber, super absorbent resin fiber, polyester fiber, polypropylene fiber, polyvinyl alcohol fiber and poly (N-isopropylacrylamide) materials are 2g, 2g, 2g, 2g, 1.4g and 0.6g respectively. According to the above preparation steps of the guide layer, the guide layer is finally obtained, which is recorded as sample seven.
[0146] Comparative Example 4
[0147] Different from the fourth embodiment, the guide layer only contains absorbent fibers and guide fibers, and the preparation surface density is 50g / m 2 The guide layer of the cotton fiber, the super absorbent resin fiber, the polyester fiber, and the polypropylene fiber are weighed in order to be 2g, 2g, 2g, and 2g. The size of the carding net of the carding machine is set to 400×400mm 2 According to the above-mentioned preparation steps of the guide layer, a guide layer was finally obtained, which was recorded as sample eight.
[0148] Carefully remove the surface layer and the guide layer of the diapers of the same brand, model and size, and cut off the elastic band and the three-dimensional edge protection, leaving only the absorbent core and the bottom film part, which are recorded as the base material. Select two base materials and cut sample one and sample two into the same size, both 100mm×200mm;
[0149] Sample 1 is laid flat on one of the substrates, and sample 7 is laid flat on sample 1, and fixed by thermal bonding. The obtained diaper body is recorded as sample A;
[0150] Sample 1 was laid flat on another substrate, and sample 8 was laid flat on sample 1, and they were fixed by thermal bonding. The resulting diaper body was recorded as sample B.
[0151] The performance of sample A and sample B was measured, wherein the dryness test and air permeability test process were as above, and the measurement data are shown in the following table:
[0152]
[0153] It can be seen from the above table that under the same surface density, for the same amount of liquid, the two infiltration times and re-infiltration amount of sample A are less than those of sample B. This is because PVA fiber and PNIPAM are added to sample A. PVA fiber has good hygroscopicity and water retention, which can further increase the water absorption speed and quickly introduce the liquid into the absorbent core. The temperature sensitivity of PNIPAM enables it to quickly absorb water at low temperatures, which helps to increase the overall absorption speed and keep the guide layer dry. PNIPAM will release water when the body temperature rises, which helps prevent liquid re-infiltration and provides additional leakage protection.
[0154] Furthermore, the air permeability of sample A is slightly higher than that of sample B. Due to the expansion effect of the super absorbent resin fiber, the air permeability of sample B will decrease after absorbing water. Although sample A will also be affected by the expansion effect, PVA fiber and PNIPAM are added. The air permeability of these materials is relatively good, and the temperature sensitivity of PNIPAM helps to regulate the local temperature, thereby improving the overall air permeability and further improving the comfort of the baby's skin.
[0155] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. Intelligent adjustable baby diaper, characterized in that: The diaper body comprises the following components from the inside out: Surface layer: including a contact layer and a release layer. The contact layer is in direct contact with the baby's skin and is responsible for cleaning and absorption. The release layer is located under the contact layer and contains skin care ingredients. The contact layer and the release layer are fixed by ultrasonic bonding. Diversion layer: absorbs the liquid in the surface layer and diffuses it downward, including absorption fibers, diversion fibers and regulating fibers; Absorbent core: absorbs and locks urine, made of a composite of highly absorbent resin and wood pulp fiber; Back layer: It is composed of a breathable microporous membrane and a bottom layer.
2. The intelligent adjustable baby diaper according to claim 1, characterized in that: The contact layer comprises: The upper layer is composed of a composite spunlace nonwoven material, which is composed of cotton fiber, polylactic acid fiber and cellulose nanofiber material. The total weight of the upper layer is 100%, and the cotton fiber, polylactic acid fiber and cellulose nanofiber account for 40-60%, 30-50% and 5-10% respectively. Lower layer: composed of viscose spunlace nonwoven material made of viscose fibers.
3. The intelligent adjustable baby diaper according to claim 1, characterized in that: The release layer is made of composite plant essence fiber material; The composite plant essence fiber material comprises aloe fiber, jojoba oil essence fiber and shea butter essence fiber. Taking the total weight of the composite plant essence fiber material as 100%, the proportions of aloe fiber, jojoba oil essence fiber and shea butter essence fiber are 40-50%, 20-30% and 20-30% respectively. The composite plant essence fiber material is subjected to antibacterial finishing.
4. The intelligent adjustable baby diaper according to claim 2, characterized in that: The preparation steps of the composite spunlace nonwoven material are as follows: A1: Wash and dry the polylactic acid fiber for pretreatment, and loosen, remove impurities and comb the cotton fiber for pretreatment; A2: adding the pretreated polylactic acid fiber and cotton fiber into a mixer according to a certain proportion and mixing them. The mixer speed is 40-80 r / min, the mixing time is 5-10 min, and the relative humidity is controlled at 30-60% to obtain a mixture 1; A3: Keeping the mixture 1 in a mixing state in the mixer, adding cellulose nanofiber powder to the mixture 1, and continuing to mix for 5-10 minutes to obtain a mixture 2; A4: Use a carding machine to card the mixture into a fiber web, and lay the carded fiber web on a conveyor belt to obtain an upper fiber web layer; A5: Use a hydroentanglement reinforcement machine to reinforce the upper fiber mesh layer, the water flow pressure is 50-200 bar, and the water flow impact time in each area is 5-30 seconds to obtain product 1; A6: Use a point-shaped thermal bonding machine to perform local thermal bonding on product 1, the thermal bonding temperature is 150-180°C, and the time for each bonding point is 10-60ms to obtain product 2; A7: Dry, cut and slit the second product to finally obtain a composite spunlace nonwoven material.
5. The intelligent adjustable baby diaper according to claim 2, characterized in that: The preparation steps of the viscose spunlace nonwoven material are as follows: B1: opening, combing and laying the viscose fibers to obtain a lower fiber web layer; B2: The lower fiber web layer is pre-treated by spray wetting, and then reinforced by a hydroentanglement reinforcement machine, with a water flow pressure of 50-200 bar and a water flow impact time of 5-30 seconds in each area, to obtain an initial lower layer; B3: The initial lower layer is subjected to vacuum water absorption and hot air drying treatment at a drying temperature of 80-120° C., and finally cut and slit to obtain a viscose spunlace nonwoven material.
6. The intelligent adjustable baby diaper according to claim 2, characterized in that: The steps of preparing the contact layer are as follows: C1: 40-60g / m 2 The viscose spunlace nonwoven material is laid flat, and the composite spunlace nonwoven material is superimposed on the surface of the viscose spunlace nonwoven material to obtain a superimposed layer; C2: Use a bonding machine to bond the four sides of the stacked layer, and use a laser etching machine to punch holes, with a mesh diameter of 2-4 mm and a mesh spacing of 0.3-0.8 mm, to finally obtain a contact layer.
7. The intelligent adjustable baby diaper according to claim 2, characterized in that: The antibacterial finishing steps of the composite plant essence fiber material are as follows: D1: Add tea polyphenol solid powder into a container, add deionized water, stir and dissolve to prepare a tea polyphenol solution; D2: Add nano zinc oxide powder and polyethyleneimine to the tea polyphenol solution and stir, and use an ultrasonic oscillator to stir for 3-10 minutes to obtain a mixed solution; D3: Immerse the composite plant essence fiber material in the mixed solution for 8-12 hours, then take it out and dry it at a temperature of 50-70°C for 20-40 minutes.
8. The intelligent adjustable baby diaper according to claim 1, characterized in that: In the guide layer: The absorbent fibers include cotton fibers and super absorbent resin fibers, which account for 50-60% and 40-50% respectively, based on the total weight of the absorbent fibers themselves being 100%; The flow-guiding fibers include polyester fibers and polypropylene fibers, which account for 50-60% and 40-50% respectively, based on the total weight of the flow-guiding fibers themselves being 100%; The regulating fiber is polyvinyl alcohol fiber and poly N-isopropyl acrylamide material, and the proportions are 60-70% and 30-40% respectively, based on the total weight of the regulating fiber itself being 100%; Taking the total weight of the guide layer as 100%, the proportions of absorption fibers, guide fibers and regulating fibers are 35-45%, 35-45% and 10-20% respectively.
9. The intelligent adjustable baby diaper according to claim 8, characterized in that: The preparation steps of the guide layer are as follows: E1: Pour the absorbent fiber and the diversion fiber into a container according to a proportion, and mix them using a mixer to obtain a mixed material; E2: Spreading the mixed material into a mesh structure through an opener and a carding machine to obtain a mesh material; E3: The mesh material is melted by heating and pressurizing, and a firm connection is formed after cooling to obtain a molding material 1; E4: combing the adjusted fibers and performing heating and pressurizing treatment to obtain a second molding material; E5: Lay the molding material 1 flat on the molding material 2, and bond the molding material 1 and the molding material 2 by a laminating machine to obtain an initial guide layer; E6: Fix the initial guide layer on the workbench, use a laser punching machine to punch holes on its surface, and finally obtain the guide layer.
10. The intelligent adjustable baby diaper according to claim 9, characterized in that: The production process of the diaper body is as follows: F1: Unwind the backing layer from the unwinder and lay it on the production line; F2: Lay the absorbent core on the surface of the back layer and extrude it using a molding machine to form a molded composite body; F3: Lay the guide layer flat on the surface of the composite body 1, and bond the guide layer and the composite body 1 by a laminating machine to obtain the composite body 2; F4: Lay the surface layer flat on the surface of the second composite body, bond the surface layer and the second composite body together through a laminating machine, and cut and trim them to obtain a diaper main body.